DETERMINANTS OF IPOS UNDERPRICING LEVEL: EVIDENCES FROM THE U.S. STOCK MARKET - Pan, Xiaoyuan (2010)
A puzzle regarding initial public offerings (IPOs) is the motivation of the issuers/underwriters “leaving the money on the table to the investors”. Numerous theoretical and empirical models explaining this underpricing phenomenon in the financial markets, they mainly focus on the asymmetric information problems, control and ownership considerations, behaviour consideration and lawsuit avoidance. I examined the extent to the determinants of initial returns based on 1,017 IPOs data in U.S. market over 1999 – 2009, shown the existence of underpricing phenomenon in U.S. with the 18.78% initial return. My results indicate that about 36.73% of the variation of initial return can be predicted by public information (or historical IPO data available online) known before the new shares offering date. Amongst various traditional explanation of the underpricing level, behaviour consideration which including the macroeconomic environment and the IPO market condition I the most significant predictors of underpricing degree. Additionally, initial return of IPOs tends to have a regular pattern.